Menguatkan Kewarganegaraan Budaya Masyarakat Adat dalam Konteks Identitas Hukum di Indonesia - Moch. Yasir Sani (Institut Kewarganegaraan Indonesia, 2025)
This paper explores the strengthening of cultural citizenship among indigenous peoples within the context of legal identity in Indonesia. Citizenship is no longer understood merely as a formal legal status but as a socio-cultural and political dimension that shapes the relationship between citizens and the state. Using a qualitative–critical approach through literature review, this study examines the theories of cultural citizenship (Rosaldo, 1994) and applies them to Indonesia’s indigenous communities, as recognized in the 1945 Constitution (UUD 1945) and national policies such as the Rencana Pembangunan Jangka Panjang Nasional (RPJPN) 2025–2045. The analysis reveals that although the formal recognition of indigenous peoples is constitutionally guaranteed, its implementation faces structural and cultural barriers. A more inclusive and participatory model of citizenship is needed—one that positions indigenous peoples as subjects of development and holders of collective rights over identity, land, and culture. Thus, cultural citizenship in Indonesia represents a political and social praxis that affirms diversity as the foundation of justice and substantive democracy.